Lesions of the lateral pterygoid muscle—an overestimated reason for temporomandibular dysfunction: a 3T magnetic resonance imaging study. Issue 12 (December 2020) - Stimmer, H.; Grill, F.; Goetz, C.; Nieberler, M.; Ott, A.; Wirth, M.; Rummeny, E.J.; Wolff, K.D.; Kolk, A.
Abstract: The aim of this study was to examine the lateral pterygoid muscle (LPM) parenchyma, myotendinous junction, and tendon in temporomandibular disorder (TMD) patients using 3T magnetic resonance imaging (MRI). Results were compared with findings reported in the literature, in which the LPM has been attributed a major role in triggering TMD. 3T MRI was used for temporomandibular joint (TMJ) imaging. The MRI images of 63 patients were analysed for muscle contracture and atrophy, tendon rupture, signal alterations of the tendon, tendon contrast enhancement, and peritendinous fluid collection. Descriptive statistics and the coefficient estimate method were used for statistical analysis. Focus was placed on the association between LPM tendon pathology and TMJ lesions like osteoarthritis and disc displacement. Severe lesions of the LPM tendon and muscle parenchyma, like rupture or fibrosis, were detected in very few cases. Only moderate signs of tendinosis were found in TMD patients. In contrast, there was a clear correlation between tendon lesions and osteoarthritis or anterior disc displacement. These results indicate the need to discuss and question the role of the LPM and its tendon in TMD. Data suggest that LPM and tendon lesions are part of complex degenerative changes of the TMJ, and it seems less likely that a LPM disorder is causative in TMD.